(untitled) - Bethel, Dayle M. (New York,Tokyo, 1973)
Tsuneasburo Makiguchi (1871-1944) was one of Japan's most significant educators, who in the 1930s proposed educational reforms that were as revolutionary as those advanced by his American counterpart John Dewey. This book tells of his contribution to education. His opposition to rote memorization, his emphasis on the creative potential of every student and his call for the involvement of community members in the educational process are ideas being broached in Western discussions about education. --This text refers to an out of print or unavailable edition of this title.
Keywords: Makiguchi, Tsunesaburo, 1871-1944,Education; Philosophy